Uptake of cholesterol by Tetrahymena thermophila is mainly due to phagocytosis - Elguero, María Eugenia (2018)
The free-living ciliate Tetrahymena thermophila is a unicellular model organism in which landmark biological processes have been discovered, such as the first description of telomerase activity and the molecular structure of telomeres, the mechanism of self-splicing RNA and ribozymes, the function of histone acetylation in transcription regulation and a number of pioneer experiments on the interference (RNAi) mechanism for programmed genome rearrangements, among others...